2021
DOI: 10.1007/s00592-021-01787-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenetic variants and response to diet/lifestyle intervention in obese subjects: a pilot study

Abstract: Aims Nutritional and lifestyle interventions can contribute to prevent and treat obesity and its complications; however, genetic background may influence the success of a therapy. The aim of this pilot study is to evaluate the effects of the interaction between nutrigenetic variants and nutritional intervention, as well as the changes in clinical parameters and the adherence to Mediterranean diet (MedDiet) and to physical activity, of 18 overweight or obese subjects affected by T2D or dysglycemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Vähämiko et al were the first to study how probiotic supplements modified DNA methylation throughout pregnancy in promoters for obesity-related genes in both mothers and their offspring [69]. In particular, the authors showed that probiotic supple-mentation during pregnancy may be able to modify the DNA methylation level in the promoter of women's FTO gene, that is, the gene most strongly associated with obesity, body mass index, and T2D in several studies [70,71].…”
Section: Epigenetic Effects Of Supplements In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Vähämiko et al were the first to study how probiotic supplements modified DNA methylation throughout pregnancy in promoters for obesity-related genes in both mothers and their offspring [69]. In particular, the authors showed that probiotic supple-mentation during pregnancy may be able to modify the DNA methylation level in the promoter of women's FTO gene, that is, the gene most strongly associated with obesity, body mass index, and T2D in several studies [70,71].…”
Section: Epigenetic Effects Of Supplements In Pregnancymentioning
confidence: 99%
“…Vähämiko et al were the first to study how probiotic supplements modified DNA methylation throughout pregnancy in promoters for obesity-related genes in both mothers and their offspring [69]. In particular, the authors showed that probiotic supplementation during pregnancy may be able to modify the DNA methylation level in the promoter of women's FTO gene, that is, the gene most strongly associated with obesity, body mass index, and T2D in several studies [70,71]. In addition, Vähämiko et al found hypomethylation both in the promoter for insulin-like growth factor-binding protein-1 (IGFBP1) and for MSRA (methionine sulfoxde reductase A) In addition, Vähämiko et al found hypomethylation both in the promoter for insulinlike growth factor-binding protein-1 (IGFBP1) and for MSRA (methionine sulfoxde reductase A) in both mothers and their offspring from the group that was administered probiotics.…”
Section: Epigenetic Effects Of Supplements In Pregnancymentioning
confidence: 99%
“…The group-based intervention was crucial to involve the participants in improving their lifestyle. This educational and nutritional program included three main goals to achieve, as previously described [29]: (i) improve the composition of meals, prioritising vegetables as well as whole foods and limiting highly processed foods; (ii) weight loss of at least 7-10%; (iii) plan at least 150 minutes a week of moderate intensity physical activity [25][26][27][28]30].…”
Section: Educational and Nutritional Interventionmentioning
confidence: 99%
“…Candidates that might modify the effect of water intake on adiposity include single-nucleotide polymorphisms (SNPs) in obesity-associated genes including, representatively SNPs in the fat mass and obesity-associated gene (FTO) (rs9939609, T>A) [6][7][8], near the melanocortin 4 receptor gene (MC4R) (rs17782313, T>C) [9][10][11], in brain-derived neurotrophic factor gene (BDNF) (rs6265, C>T) [12,13]. Previous studies have shown that these genetic variations are implicated in obesity risk by modulating energy intake and energy expenditure [14][15][16].…”
Section: Introductionmentioning
confidence: 99%